Digital Diplomacy and People’s Power: Reframing India–Maldives Relations in the Era of Social Media Governance - Paul, Anurag (Unisia, 2025)
India and the Maldives have historically shared a relationship marked by fluctuating tides, but the diplomatic chill following the election of Maldivian President Mohamed Muizzu—widely perceived as anti-India—signaled a sharp downturn. Tensions escalated when senior Maldivian officials made derogatory comments about Indian Prime Minister Narendra Modi and mocked the government's efforts to promote Lakshadweep as a tourism destination. What followed was not just a state-to-state fallout, but a nationwide digital backlash. Indian citizens, leveraging social media platforms, initiated a widespread boycott of Maldivian tourism—a sector crucial to the island nation's economy. The economic ramifications were immediate and severe, leading to a diplomatic recalibration. In a striking reversal, President Muizzu extended an invitation to Prime Minister Modi to attend the Maldives’ 60th Independence Day celebrations as Guest of Honour, signaling a thaw driven not by elite diplomacy, but by popular digital dissent. This paper argues that this episode marks a transformative moment in India’s foreign policy architecture—where We the People of Bharat, through digital activism, public sentiment, and consumer choices, directly influence regional diplomacy. By framing this case as a paradigmatic shift from elite-driven diplomacy to people-powered digital governance, this paper interrogates how public sentiment, algorithmic visibility, and consumer nationalism shape contemporary geopolitical realignments. Situating this within the broader themes of governance transformation and regional diplomacy, the paper contends that digital publics now serve as critical actors in foreign policy processes, where statecraft is increasingly responsive to networked publics and the algorithmic amplification of national sentiment.